Deconstructing myths and reallocating borders: Contributions of clinical psychology beyond the office - Pires, Sergio Fernandes Senna (Seven Editora, 2024)
In this theoretical essay, we address the need to reposition Clinical Psychology, highlighting its challenges when it is confined by prejudices that limit it to the application of its knowledge to traditional therapeutic spaces. We reflect on the need to overcome, even if partially, the fragmentation of psychological knowledge in order to promote the development of more integrative approaches. We highlight the resistance arising from the generic association of Clinical Psychology with the medical model or with the dichotomy of health versus disease. In order to confront this misconception, we highlight the importance of carrying out an integrative articulation between the knowledge constructed in various fields of Psychology. We bring examples to show the need to use innovative strategies in the integration of transversal and heterodox approaches, including contributions from Clinical Psychology in this regard. The application of adaptable clinical techniques to non-traditional contexts, such as Psychodrama in socio-emotional education, is highlighted, evidencing the relevance of this adaptation for coping with issues such as violence and the deconstruction of prejudices. It is concluded that the promotion of a more integrative Psychology is essential to deepen knowledge and find solutions to complex problems. By challenging prejudices and broadening the scope of application of practical-scientific knowledge from Clinical Psychology, we highlight its potential to contribute to the construction of a more comprehensive understanding of the human being. DOI:https://doi.org/10.56238/sevened2023.007-074